Narrative Influence in the Digital Age: How Digital Literature Shapes Consumer Behavior - Ahmad Taufiq (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2021)
In the digital era, literature has transcended conventional print to include interactive, multimodal, and participatory storytelling formats. This change has engendered digital literature, a genre that increasingly converges with consumer culture. Despite the increasing ubiquity of narrative-driven content in digital contexts, the impact of digital literature on consumer behavior remains little examined. This study seeks to analyze the influence of digital literary narratives on customer attitudes, identity, trust, and decision-making. The study utilizes a critical review process to combine findings from peer-reviewed, Scopus-indexed journals in marketing, psychology, and digital humanities. The analysis identifies four principal themes: (1) narrative immersion amplifies emotional engagement and receptiveness to marketing messages; (2) digital literature functions as a symbolic resource for identity formation and lifestyle congruence; (3) narrative coherence and authenticity cultivate trust in digital content; and (4) literary narratives affect consumer decisions via both affective and cognitive processes. These findings indicate that digital literature is not simply a cultural artifact but a tactical medium for consumer persuasion. The research enhances interdisciplinary scholarship by merging literary theory with consumer behavior studies and provides actionable insights for marketers and content providers aiming to captivate consumers through narrative. Future study should empirically validate these conclusions through experimental and longitudinal methodologies.